2010
DOI: 10.1016/j.ijgo.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cervical neoplasia in Bangladesh using visual inspection with acetic acid

Abstract: A VIA-based program would facilitate the development of screening, diagnosis, and treatment of cervical neoplasia and improve awareness of cervical cancer prevention in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 9 publications
1
50
1
1
Order By: Relevance
“…GOB has a plan to make it a nation-wide program. VIA is performed at Maternal and Child Welfare Centres (MCWCs) Senior Staff Nurses (SSNs) and Doctors (Ahmed et al, 2008;Nessa et al, 2010). The services for cervical and breast cancer screening are currently available as opportunistic screening at 252 facilities including BSMMU, 14 MCHs, 57 DHs, 61 MCWCs, 15 (out of 482) Upazila Health Complexes (UHC), 44 (out of 3725) Union Health & Family Welfare Centers (UH&FWC), 25 Urban Primary Health Care centers and 35 Non-Government Organizations (NGO).…”
Section: Introductionmentioning
confidence: 99%
“…GOB has a plan to make it a nation-wide program. VIA is performed at Maternal and Child Welfare Centres (MCWCs) Senior Staff Nurses (SSNs) and Doctors (Ahmed et al, 2008;Nessa et al, 2010). The services for cervical and breast cancer screening are currently available as opportunistic screening at 252 facilities including BSMMU, 14 MCHs, 57 DHs, 61 MCWCs, 15 (out of 482) Upazila Health Complexes (UHC), 44 (out of 3725) Union Health & Family Welfare Centers (UH&FWC), 25 Urban Primary Health Care centers and 35 Non-Government Organizations (NGO).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of VIA based screening programs into national programs is already taking place in many low and middle income countries and the evaluation of its impact on the service delivery will largely determine the success of the program when introduced into routine healthcare. (15,16,17) VIA is a simple and affordable screening test with acceptable sensitivity and specificity in the range 50-88.6% and 66.7-89.7%, respectively, in a research setting. (20) We report 3 year experience of VIA /VILI done during routine gynaec exam for every women coming to the OPD as an extension of gynaecological exam and its feasibility and usefulness in detection of cervical precancer and cancer lesions as well as other lower genital tract lesions .in a rural population where no organised screening program existed and with introduction of this simple measure we have been able to downstage cervical cancer from stage ¾ to early stage and CIN With no added cost and no additional infrastructure and personel.…”
Section: Discussionmentioning
confidence: 99%
“…Figures between 2.9% and 27.4% have been reported. [11][12][13][14][15] There is no agreement or evidence to suggest an ideal rate. However, it is suggested that if VIA positivity is less than 5%, it is likely that lesions are missed when refresher training for the providers should be arranged.…”
Section: Discussionmentioning
confidence: 99%
“…A further advantage of this technique is the ability to offer treatment the same day; the so-called see and treat policy, which improves compliance and yields reasonable screening outcome. [10][11][12] However, its main limitation is a high rate of false-positive results, which may lead to overtreatment if this policy is applied. 9 The objective of this study was to assess feasibility and suitability of VIA as a cervical cancer screening modality in an underresourced setting in a developing country, and compare it with Papanicolaou test.…”
mentioning
confidence: 99%